Dual pandemics? Assessing associations between area racism, COVID-19 case rates, and mental health among U.S. adults - Rachel Donnelly; Brazil Remani; Christy L. Erving (Elsevier, 2023)
Mental health worsened during the COVID-19 pandemic, especially among racially minoritized adults. Population-level racial attitudes, or area racism, may be associated with mental health, particularly during this historical moment, but this possibility has not been tested in prior research. In the present study, we use nationally representative data from the Household Pulse Survey (April-October 2020) to document associations between area racism and depression/anxiety in the United States among non-Hispanic Black, non-Hispanic Asian, Hispanic, non-Hispanic White, and other racial/ethnic minority adults. We further consider the national COVID-19 case rate to examine an additional macro-level stressor. Findings indicate that area racism was positively associated with depression and/or anxiety for Black, Hispanic, White, and other racial/ethnic minority adults. Moreover, COVID-19 cases posed an additional, independent mental health threat for most groups. This study points to area racism as a macro-level stressor and an antecedent of mental health for racially diverse groups of Americans.